A morphological, phylogenetic and phylogeographic reappraisal of the land crabs Gecarcinus quadratus De Saussure, 1853, and G. lateralis Fréminville in Guérin, 1832 (Decapoda: Gecarcinidae). Are they different species? - Toledano-Carrasco, Ia Atzimba; Villalobos, José Luis; Álvarez, Fernando (Zootaxa, 2021)
Land crabs of the genus Gecarcinus are distributed along both versants of the American continent. At some point four species were recognized: G. lateralis, G. nobilii, G. quadratus, and G. ruricola. Taxonomically, several authors have tried to differentiate Gecarcinus lateralis from the Atlantic coast and G. quadratus from the Pacific coast. Because morphologic characters used showed high intra-population variability, identification were very difficult. Consequently, these two species have occasionally been considered synonyms. To establish the degree of genetic difference between them a molecular analysis was performed with both species, G. lateralis and G. quadratus, including Mexican Pacific and Atlantic specimens, using the mitochondrial COI and 16S genes. The maximum clade credibility and maximum likelihood trees showed two clades with high support values, one corresponding to the Gulf of Mexico population and the other one to the Pacific coast population, with a genetic distance of 6.1%. The within-clade average distance for the Atlantic populations (G. lateralis) was 1.1% and 0.2% for those of the Pacific coast (G. quadratus). This supports the status of G. quadratus as a valid species, not as a synonym of G. lateralis. The estimated time of divergence between both species ranged between 2.3 to 4.3 million years, coinciding with the proposed closure of the Isthmus of Panama. Morphologically, some populations show high variability in somatic characters, whereas sexual appendices of males of both species showed very little variation. Color in life, shape of sternite 3, and shape and degree of coverage of the abdomen of thoracic sternites, in both sexes, are traits that can be used to differentiate both species.